70 The digital ambulance: electronic patient clinical records in prehospital emergency care. (16th April 2018) - Porter, A; Potts, H; Mason, S; Morgan, H; Morrison, Z; Rees, N; Shaw, D; Siriwardena, N; Snooks, H; Williams, V
Abstract : Aim: Electronic Records in Ambulances (ERA) is a two-year study examining the opportunities and challenges of prehospital implementation of electronic patient clinical records (ePCR) in the UK. National policy encourages digitisation of health services, 1 but this transition may not be straightforward. 2 Method: A telephone survey of progress implementing ePCR in all 13 UK ambulance services explored systems, implementation processes, perceived value and future plans. Interviews with information managers were thematically analysed. Case studies in four UK ambulance services involved observing clinical work, focus groups with ambulance clinicians, interviews with key stakeholders and analysis of routine data. Results: Baseline survey: 7/13 services were using ePCR, with mixed compliance from staff. Reported benefits concerned improved data access for audit. Of the 6/13 services currently using paper records, four had previously adopted ePCR, but reverted. Case studies: Initial findings suggest some common themes: Constant change: 3/4 services were already undertaking or considering transition to a second generation system; 1/4 was undertaking a phased rollout of ePCR. Digital diversity: no standard hardware or software in use. Indirect input: patient data was still sometimes transferred to the ePCR from another source (eg writing on a glove) or entered retrospectively. Data dump: ePCRs acted mainly as a store, rather than transferring information to other care providers or supporting decision making. Conclusion: Although ePCRs offer opportunities to support prehospital care, the transition to the new technology is neither linear nor co-ordinated, with full benefits not yet realised in terms of integration and data sharing. References: . Wachter RM. Making IT work: Harnessing the power of health information technology to improve care in England 2016. Report of the National Advisory Group on Health Information Technology in England. . Greenhalgh, Potts H, Wong G, Bark P, Swinglehurst D. Tensions and paradoxes in electronic patient record research: A systematic literature review using the meta-narrative method. Milbank Quarterly2009;87(4):729–788. Conflict of interest: None Funding: UK National Institute for Health Research.